Influência da amplitude de deformação e da deformação acumulada na evolução microestrutural e comportamento mecânico do cobre processado por forjamento multidirecional - Paula Cibely Alves Flausino (2021)
Severe Plastic Deformation (SPD) processes have been widely studied as tools for obtaining metals and their alloys with high mechanical strength associated with grain refining down a submicrometric size and the introduction of high dislocation density. Among these processes, Multidirectional Forging (MDF) is one of the simplest and can be readily applied in the industry. In this context, this work aims to investigate the influence of strain amplitude (∆ε) and accumulated strain (ε) on the microstructural evolution and mechanical behavior of commercial-purity copper (99.8%) processed at room temperature by Multidirectional Forging (MDF) with Δε ≈ 0.075, 0.15 and 0.30 up to ε ≈ 10.8. The shape of the cumulative flow curves is similar to other results where dynamic recovery prevails, with a region of hardening in the initial stage of deformation and a practically stationary aspect, with a practically constant flow stress for higher values of ε. Deformation-induced microstructural changes involve the progressive evolution of dislocation structures with low disorientation angles towards structures with high disorientation. This evolution is assisted by dynamic recovery processes and is influenced by the formation and intersection of micro shear bands (MSBs). Thus, the grain refining induced by straining in MDF, occurs in a progressive and heterogeneous process and is strongly influenced by the strain amplitude per pass (∆ε). Rising ∆ε increases the “monotonic” character of MDF, involving more MSBs and their intersections, higher dislocation densities, higher fraction of sub-micrometric grains, smaller average size of substructures and an acceleration (in terms of accumulated strain) of the grain refinement kinetics, in comparison with MDF with low strain amplitudes. As a consequence, saturation stresses increase as ∆ε is raised. On the other hand, the 0.2% yield strength of the material (σy) is substantially below the flow stress observed at the end of the previous compression step. This behavior is similar to a “Bauschinger effect” and is more prominent for larger values of ε and ∆ε in MDF.